2023
DOI: 10.1177/09603271231211894
|View full text |Cite
|
Sign up to set email alerts
|

The effects of esketamine on the intestinal microenvironment and intestinal microbiota in mice

Ying Zhang,
Wenhao Ma,
Hao Lin
et al.

Abstract: Objective This study aimed to investigate the impact of esketamine on the intestinal flora and microenvironment in mice using mRNA transcriptome sequencing and 16S rRNA sequencing. Methods Ten female mice were randomly assigned to two groups. One group received daily intramuscular injections of sterile water, while the other group received esketamine. After 24 days, the mice were sacrificed, and their intestinal tissues and contents were collected for 16S rRNA sequencing and mRNA transcriptome sequencing. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…Remarkably, S-ketamine exerts neuroprotective effects via enhancing autophagy and lessening oxidative stress; the mechanism comprises AMPK/mTOR-dependent autophagy and/or the antioxidant system [78]. Amazingly, Sketamine significantly altered the abundance of intestinal microbiota including Adlercreutzia equolifaciens and Akkermansia muciniphila [79]. It has been revealed that the regulation of NFAT signaling by miR-149 might play a role in the tenacious prophylactic effects of Rketamine in inflammation, and that gut microbiota can regulate the gene expression of miRNAs via the gut-brain axis [80].…”
Section: A Possible Tactic With Alteration Of Gut Microbiota Against ...mentioning
confidence: 99%
“…Remarkably, S-ketamine exerts neuroprotective effects via enhancing autophagy and lessening oxidative stress; the mechanism comprises AMPK/mTOR-dependent autophagy and/or the antioxidant system [78]. Amazingly, Sketamine significantly altered the abundance of intestinal microbiota including Adlercreutzia equolifaciens and Akkermansia muciniphila [79]. It has been revealed that the regulation of NFAT signaling by miR-149 might play a role in the tenacious prophylactic effects of Rketamine in inflammation, and that gut microbiota can regulate the gene expression of miRNAs via the gut-brain axis [80].…”
Section: A Possible Tactic With Alteration Of Gut Microbiota Against ...mentioning
confidence: 99%